Perencanaan Ulang Jembatan STA 14+633 – 14+750 pada Proyek Pembangunan Jalan dan Jembatan Lot 1B Brumbunm Bantai Sine Kabupaten Tulungagung dengan implementasi BIM 5D - Dimas Fernanda Bagus Dwi Prastiyo; Muhamad Irsyad Cesianto; Asri Nurdiana; Bambang Setiabudi (Jurnal Proyek Teknik Sipil, 2026)
The planning of the bridge employing Building Information Modeling (BIM) technology yields an integrated, systematic, and comprehensive design, with a strong emphasis on efficiency. BIM encompasses modeling dimensions from 3D up to 7D, enabling multiple stakeholders to analyze and rectify any discrepancies relative to the originally planned project, whether identified by the owner or the contractor, thereby mitigating potential delays. This capability is made possible by BIM’s ability to digitally visualize all project activities. The redesign of the bridge at Sta 14+633 – 14+750, within the Lot 1B Brumbun – Pantai Sine Road and Bridge Construction Project in Tulungagung Regency, was executed using 5D BIM. This implementation integrates Autodesk Revit and Autodesk Navisworks for 3D modeling, 4D construction scheduling evaluation, and 5D cost estimation analysis. The outputs of this planning process include detailed 2D Detail Engineering Design (DED) drawings, 3D visualizations through still images and animated videos, and 4D construction schedule simulation animations. Furthermore, the infrastructure cost plan is prepared in a 5D format, integrating cost estimation with the project model to facilitate more precise and reliable analyses.